ANTIOXIDANT ACTIVITY OF EXTRACT COMBINATION FROM Averrhoa bilimbi L. LEAVES AND STINGLESS BEE HONEY - Bunga Putri Sari; Paula Mariana Kustiawan (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Belimbing wuluh (Averrhoa bilimbi L.) leaves and stingless bee honey contains phenolic compounds that can act as antioxidants. This study aims to find out the antioxidant activity of extract combination from stingless bee honey (Trigona spp.) and Belimbing Wuluh (Averrhoa bilimbi L.) leaves. This research was used DPPH (2,2-diphenyl-1-picrilhidrazyl) method. Then measured by UV-VIS spectrophotometry. The results showed the greatest IC50 of extract combination from stingless bee honey and Averrhoa bilimbi L. leaves was 2:1 (90,36 ppm) and was classified as strong activity. This activity was influenced by the synergistic effect between the combination of secondary metabolites contained therein.